Simulation study of an EBG-M applicator towards non-invasive breast hyperthermia cancer procedure - Lias, K.; Buniyamin, N.; Narihan, M.Z.A. (UTM Press, 2016)
Interest in the development of hyperthermia for cancer procedure is growth explosively all over the years as it is able to damage and kill the cancer cell non-invasively. An EBG-M antenna is designed with FDTD simulation packages, which is then applied towards treated cancerous area, where for the purpose of this simulation studies, breast is developed as the targeted cancer area to be treated. The radiation absorption is presented as the results obtained to be compared with previous works and also to be analyzed. It has been recognized that the designed antenna or also called as the applicator is able to offer depth radiation absorption and also improved the focusing, which is represented by the specific absorption rate (SAR) distribution towards breast hyperthermia cancer procedure.